Squamous cell lung cancer: genomic evolution and personalized therapy - Andrés F Cardona; Luisa Ricaurte; Zyanya Lucia Zatarain-Barrón; Oscar Arrieta (Instituto Nacional de Salud Pública, 2019)
Objective. To review the state-of-the-art in relation to the current information on squamous cell lung cancer (SCLC). We describe the genetic anomalies reported, their effect, and finally the most promising therapeutic agents. Materials and methods. We reviewed published articles in peer-reviewed journals as well as current treatment guidelines from local and international resources. Results. SCLC represents a smaller proportion of the global burden of disease for lung cancer compared to its more frequent presentation, the adenocarcinoma. However, more than 400 000 cases are reported annually, a substantial population for whom therapeutic options are scarce and with limited efficacy. Several groups have been given the task of elucidating the mechanisms that lead to the development of SCLC, including molecular anomalies that can be used as targets for drug design. Conclusion. There are potential therapeutic targets for SCLC, which must be studied in clinical trials for validation.